Stories in Law School: An Essay on Language, Participation, and the Power of Legal Education - Praagh, Shauna Van (Columbia Journal of Gender and Law, 1992)
In the fall of 1986, the entering law school class at Queen’s University was greeted with an orientation address by Professor Toni Pickard. Professor Pickard welcomed the students by saying that law school is part of real life, rather than being a “way-station on the route to something else” and that the students were responsible for being active members of their new community during their tenure. She then introduced the class to the hierarchical organization of law school and warned them about the devaluation of personal knowledge that results from that structure: You may, most likely will, find your classes proceeding as if nothing you studied before, nothing you have learned through your life experience, is relevant. They also tend to proceed as if none of the wide differences among your professors’ backgrounds, commitments, and life experiences is relevant. This too creates a sense that The Law is There-even a pressure to see it that way- that Law is a thing to be grasped, and each of us has to put our self aside, has to understand It for what It is. But that is not right. It is right that there are certain understandings shared by most of those engaged with law-that legal stances, decisions, arguments have a certain self-understanding, and that law teachers are out to impart their own understanding of these self-understandings. But like any individual’s understanding of him or herself, these self- understandings are only partial.